Tentzel and the elephant in the room. Inconsistencies in the history of nature and history of humans (not) being discussed when 'fossils' were found in Thuringia in 1695. - Friedrich, Susanne (Annals of Science, 2025)
In 1695 the fossils of a woodland elephant were excavated in Burgtonna (Thuringia). This article deals with the debate between Gotha's court historiographer Wilhelm Ernst Tentzel (1659–1707), who interpreted the discovery as the remains of an elephant, and the collegium medicum of Gotha, that insisted that it was a lusus naturae. The debate, in which scholars throughout Europe soon became involved, is paradigmatic for the social, professional, epistemological and religious frames that determined what around 1700 one could say and think about the history of the earth and the role humans played in it. While Tentzel, as a specialist in human history, proved that the findings of fossilized exotic animals could not be explained by human intervention and argued for the Deluge as an agent of transport, for some of his correspondents inconsistencies between human history and the history of Nature emerged at this point, and time itself became an issue. The study emphasizes the importance of regional historiography for the understanding of nature as well as the transformation of history of Nature into natural history.